Efektivitas Kewenangan Pemerintah Kota Tanjungpinang Di Bidang Kelautan Dan Perikanan Pasca Lahirnya Undang-Undang Pemerintahan Daerah - Ampuan Situmeang; Rufinus H Hutauruk; Winsherly Tan; Dian Fransisca (Wajah Hukum, 2021)
The purpose of this study is first, analyzing the authority of the Tanjungpinang City Food and Fisheries Department in conducting fishery development and coastal marine supervision after the enacting of Law No. 23 of 2014 on Local Government. Second, identify about the obstacles faced by the Food and Fisheries Department of Tanjungpinang City in conducting fishery development and coastal marine supervision after the enacting of Law No. 23 of 2014. Third, find the right solution for Tanjungpinang City Food and Fisheries Department. This study uses empirical juridical methods with a qualitative approach and the data used is secondary data From the results of the research conducted, it was obtained that in order to ensure the optimal protection of fishermen, the central government should still provide a small portion for the regency / city government to conduct surveillance in the marine sector, because most of the fishing community still considers that the Department of Agriculture, Food and Fisheries Tanjungpinang City has the authority to solve problems that are generally faced by fishermen when they go fishing.